Qualidade em serviços: foco no Modal Rodoviário de Cargas - um estudo de caso - Sousa, Ruthelle Maria de Carvalho (2011)
This dissertation presents an exploratory research and single case study, the company Mafrense Log. Transport and Storage Ltda., located in Teresina in Piauí state, on the influence of quality management focused on air cargo services in the land. Emphasizes the importance of logistics in the road, because it is composed it is composed of between who supplies, distributes and uses, focusing also on processes, which begins in demand, with order processing, customer and product information, storage, transport, system back in their packaging and logistics process as all the flows of information that put the products or services on the move, the purpose of providing adequate service levels to customers more quickly and at reasonable costs. The logistics for the delivery of services defines the main activities and support, in which the main ones are: transportation, inventory maintenance and order processing. The focus in the transport activity is to be hanling both raw materials and the finished product and considered by many in the business life, due to its importance in logistics costs, absorbs about two thirds of these costs. Relating to the Quality Management, are directly influenced the consumer requirement, that each day increases your level of expectation and need, factors that contribute to causing companies to seek new forms, techniques and ways to serve customers both internal and external thus the study of quality services in road transportation of cargo, with parameters of ISO 900,9001 and 9004, with collections of semi-structured data, together with structured questionnaires, these points contributed to the assessment of quality management and reviews scoring categories, such: as process management, physical facilities, equipment, information technology, people management and customer relationship for the purpose of lean production practices, new forms of relationship between companies in the supply chain, the evolution of business over the internet, the emergence of more specialized suppliers in terms of technological advances and competition itself, causing an organizational restructuring in companies